Electronic Collection of Multilingual Patient-Reported Outcomes across Europe - Soto-Rey, I.; Rehr, M.; Bruland, P.; Zeidler, C.; Riepe, C.; Steinke, S.; Ständer, S.; Dugas, M.; Storck, M. (Methods of Information in Medicine, 2018)
Background Patient-reported outcomes (PROs) are information provided directly by patients that helps in improving patient diagnosis and treatment. Validated translations of PROs can be used to treat international patients. Electronic systems and especially mobile devices provide a great opportunity for their collection; however, these systems are normally study-oriented and therefore single language, not scalable, and not interoperable.Objectives This article reports the development of a multicenter, multilingual, and interoperable electronic PRO (ePRO) system and evaluates its user satisfaction in an international clinical study.Methods The ePRO named “MoPat2” was developed using Java 8 and jQuery Mobile 1.4.5. The system was evaluated in the context of the European dermatology project “European Network on Assessment of Severity and Burden of Pruritus”(PruNet), which aimed to unify the assessment of itch in routine dermatological care in Europe. Twenty-six clinicians and 468 patients from 8 European clinical centers were asked to complete a user satisfaction questionnaire regarding the use of MoPat2 with a tablet personal computer. The results were then analyzed and correlated with the age, gender, and language of the respondents.Results MoPat2 was enhanced with multilingual capabilities and is now able to conduct surveys in several languages, as well as store and display the results in the local language. The interviewed clinicians rated the system with an average score of 2.0 (“good”) in a 1 to 5 Likert scale. Note that 93.9% of the patients (439 of 468) reported having got on well using the system and 88.9% (416 of 456) would be willing to further use it. The age of the patients not willing to further use MoPat2 was, in average, considerably higher than the age of patients willing to use the system.Conclusions This study represents the first use of an ePRO system for the collection of multilingual PROs in an international, multicenter setting. MoPat2 has been evaluated by both clinicians and patients in the context of a European dermatological study, resulting in a high user satisfaction. The system will be further developed to include new features such as patient follow-ups outside of the clinical setting.
Keywords: patient-reported outcome measures; multilingualism; mobile health